2009
DOI: 10.1007/s11947-009-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing on Textural Kinetics in Snacks During Frying

Abstract: Kinetics of texture development during frying of snacks subjected to different initial conditions such as frozen, frozen-thawed, and unfrozen was investigated. The temperature dependency of the changes in the form of reaction constants was explained by Arrhenius equation. The increase in hardness and decrease in cohesiveness followed first-order reaction kinetics (R 2 =0.94-0.99) in all the samples. Frozen samples showed induction (phase I) and development/degradation (phase II) periods for textural parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In general, foods exhibit a zero-or first-order time dependence relationship (Maity et al 2009). It has been established by several researchers that degradation of both pigments and visual colour follow first-order reaction kinetics (Ahmed et al 2004;Wang and Xu 2007).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…In general, foods exhibit a zero-or first-order time dependence relationship (Maity et al 2009). It has been established by several researchers that degradation of both pigments and visual colour follow first-order reaction kinetics (Ahmed et al 2004;Wang and Xu 2007).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…In our earlier work, the kinetics of texture development during frying of vegetable stuffed snacks subjected to different initial conditions such as frozen, frozen-thawed, and unfrozen (Maity et al 2009) were reported. However effect of different flour formulations on the overall quality of fried snacks needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Potato chips are thin slices whose moisture content decreases from around 80% to almost 2% when they are fried (Maity et al 2009). It is worth to mention that acrylamide, a chemical compound that is formed in potatoes during frying and is highly related to the color of potato chips, has recently been found to be critical for human health since it is a carcinogenic agent in rats (Rosen and Hellenäs 2002;Mottram et al 2002;Stadler et al 2005;Pedreschi et al 2005).…”
Section: Introductionmentioning
confidence: 99%